Generation of Quasi‐Periodic Dayside Medium Scale Traveling Ionospheric Disturbances (MSTIDs) by Intermittent Lobe Reconnection - Yating Xiong; Huixin Liu; Run Shi; Zanyang Xing; Sheng Lu; Qiang Zhang; Zhiwei Wang; Desheng Han (Geophysical Research Letters)
Abstract The medium‐scale traveling ionospheric disturbances (MSTIDs) can be excited by many sources. Among those magnetic reconnection has been proposed as a potential driver for dayside MSTIDs, but direct evidence has been limited. Using ground‐based radar data from the Super Dual Auroral Radar Network on 14 December 2012, we observed quasi‐periodic multiple MSTIDs propagating from auroral latitudes to mid latitudes near magnetic local noon, which showed one‐to‐one correspondences to intermittent lobe reconnections with periodicities of about 20–30 min. Simultaneous EISCAT Svalbard incoherent scatter radar data revealed enhanced electric field and Joule heating within the cusp region following each lobe reconnection. These multi‐instrument observations strongly suggest lobe reconnection as a possible driver for the dayside MSTID.